A 57-year-old woman with chronic hepatitis B and left hepatic nodularity unmasking intrahepatic hilar adenocarcinoma: A diagnostic case report - Pramana, Triyanta Yuli; Gunawan, Timotheus A.; Prasetyo, Didik; Darmayani, Aritantri; Jati, Agus; Wasita, Brian (Faculty of Medicine, Universitas Islam Indonesia, 2025)
Metastatic breast cancer involving the biliary tract is a rare case with an incidence rate of 1.49 per 100.000 persons. Chronic hepatitis B virus (HBV) infection is associated with tumor development and migration and promotes metastasis. While hepatocellular carcinoma is the most common primary liver cancer, cholangiocarcinoma is a rarer malignancy originating from epithelial cells in various parts of the bile ducts. Intraluminal adenocarcinoma of the common hepatic duct (CHD) is an exceptionally uncommon hepatic tumor. We reported that a 57-year-old female has been complaining of abdominal pain on the upper right side for 1 year, accompanied by nausea and icterus. The patient had a history of breast cancer in 1995 and chronic hepatitis B for 20 years on Tenovofir 1x300 mg. No abnormalities were found on physical examination. However, Magnetic Resonance Cholangiopancreatography (MRCP) revealed bilateral dilatation of the intrahepatic bile duct (IHBD), common hepatic duct (CHD), ductus cysticus, and common bile duct (CBD) distal to proximal, suggesting an intraluminal mass likely due to a tumor. A plastic stent was then placed, which reduced the lesion size. Immunohistochemistry (IHC) test confirmed adenocarcinoma, in which CK-7 and mammaglobin were positive, indicating metastatic breast cancer.. A thoracic MSCT revealed multiple lytic lesions in the T1, T7, T9–T12, and L2–L3 vertebral bodies. The patient was diagnosed with intraluminal adenocarcinoma of the CHD, representing metastatic Stage I triple-negative breast cancer with biliary, pulmonary, and osseous involvement, along with chronic hepatitis B. The chemotherapy regimen included carboplatin 370 mg and paclitaxel 260 mg, continued with Taceral 500 mg 2x3 in two weeks and Zometa every 6 weeks. Post-chemotherapy MRCP evaluation showed a solid intraluminal liver lobe lesion with partial obstruction. Metastatic adenocarcinoma of the CHD caused by breast cancer is a highly unusual clinical problem. In such cases, IHC plays a vital role in identifying the primary tumor site.